Altered expression of MALAT1 lncRNA in nonalcoholic steatohepatitis Fibrosis Regulates CXCL5 in Hepatic Stellate Cells - Leti, Fatjon (Transl Res, 2017)
In the present study, we sought to identify lncRNA expression profiles in NASH patients with histological evidence of lobular inflammation and advanced fibrosis. We profiled lncRNA expression using RNA-sequencing of wedge liver biopsies from 24 NAFLD patients with normal liver histology, 53 NAFLD patients with lobular inflammation, and 65 NAFLD patients with advanced fibrosis. Transcript profiling identified 4432 and 4057 differentially expressed lncRNAs in comparisons of normal tissue with lobular inflammation and fibrosis samples, respectively. Functional enrichment analysis revealed lncRNA participation in TGFB1 and TNF signaling, insulin resistance, and extracellular matrix maintenance. Several lncRNAs were highly expressed in fibrosis relative to normal tissue, including nuclear paraspeckle assembly transcript 1 (NEAT1), hepatocellular carcinoma upregulated lncRNA (HULC), and metastasis-associated lung adenocarcinoma transcript 1 (MALAT1). Two potential target mRNAs, syndecan 4 (SDC4) and C-X-C motif chemokine ligand 5 (CXCL5) were identified for HULC and MALAT1, respectively, but only CXCL5 showed differential expression among the different histological classes. Knockdown of MALAT1 expression reduced CXCL5 transcript and protein levels by 50% and 30%, respectively, in HepG2 cells. Expression of MALAT1 and CXCL5 was upregulated in activated hepatic stellate (LX-2) cells compared to cells in the quiescent state, and MALAT1 expression was regulated by hyperglycemia and insulin in HepG2 cells, but only by insulin in LX-2 cells. Dysregulated lncRNA expression is associated with inflammation and fibrosis in NASH. Functionally relevant differences in MALAT1 expression may contribute to the development of fibrosis in NASH through mechanisms involving inflammatory chemokines.